2020
DOI: 10.1002/prp2.629
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist’s role in HIV care in France. Implication for clinical improvement of people living with HIV worldwide

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Consistent with previous international evidence, 37 when Portuguese participants were asked about the preferred setting to continue to refill their HOM, a very high proportion reported preference to continue to have access to their medication at CP, close to their home or place of work. The results highlight the importance of giving citizens freedom of choice, but also the relevant public health role performed by the network of CP in interprofessional collaboration, contributing to the system’s efficiency.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Consistent with previous international evidence, 37 when Portuguese participants were asked about the preferred setting to continue to refill their HOM, a very high proportion reported preference to continue to have access to their medication at CP, close to their home or place of work. The results highlight the importance of giving citizens freedom of choice, but also the relevant public health role performed by the network of CP in interprofessional collaboration, contributing to the system’s efficiency.…”
Section: Discussionsupporting
confidence: 67%
“…30 Indeed, the regular dispensing of specialty medicines that do not require in-hospital administration for treatment, as the case of some therapeutics for hepatitis C, HIV, multiple sclerosis, psoriatic arthritis, and others, is already provided by both the CP and HP in most jurisdictions. 31 Some examples are Australia with medicines for HIV and viral hepatitis, 32 , 33 Canada 34 with oral anticancer drugs, Belgium with immunosuppressants, 35 , 36 and France and Germany with antiretroviral therapy, 37 , 38 with CP being reimbursed for the service.…”
Section: Discussionmentioning
confidence: 99%
“…Overall status of health was not measured, which may have impacted the findings. Some participants found the self-reported adherence questionnaire to be difficult to understand, this may have affected the findings, also pharmacy-based adherence data was based on pharmacy refill data, which may not always mean participants are taking the medications they collect Jacomet et al, 2020 (France) [ 59 ] n = 1137 M = 50.2 years Hospital and community Data were collected through surveys The presence of co-morbidities was reported in 64.2% of participants and 90% had a undetectable viral load. 58% of participants knew of the medication file, however, only 40% of pharmacists reported to offering it systematically.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a study investigating the pharmacist’s role in HIV care in France reported that 21.6% ( n = 233) of participants would agree to interviews with pharmacists during ARV dispensing to improve their knowledge and help manage their ART, and 18.9% ( n = 204) would participate to improve their follow-up and compliance [ 59 ]. It was reported by 94% of pharmacists recruited in this study that more training would be required for them to manage and address the needs of PLWH [ 59 ]. One study using patient and provider focus groups found that healthcare providers need a deeper knowledge base to care for the ageing HIV population [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacists, who play an increasingly important role in HIV care delivery for PLHIV, assert that ART drug stock management will need to be carefully planned [17]. Pharmacies would need a broader inventory to cover the many two-drug and three-drug combination therapies on the market, and yet they could also end up reducing their stock inventory by ordering per-patient only.…”
Section: Introductionmentioning
confidence: 99%